Pengaruh Struktur Good Corporate Governance Terhadap Kinerja Keuangan Bank Perkreditan Rakyat (studi Kasus Pada Bpr Di Provinsi Jawa Barat Periode 2017) - Euodia Pracinthea; Djuminah Djuminah (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2019)
BPR’s financial performance has been continuously improved, one of which is by intensifying GCG (good corporate governance) implementation. GCG is considered capable of being a means for BPR to maintain the continuity of BPR operations and to minimize the level of liquidation phenomenon continues today. The purpose of this study is to know the impact or the influence of GCG structure on the BPR’s performance as measured by the ROA .The secondary data is used,. The results of this study is BPR governance’s structure that’s proxied by the number of directors has a positive significant impact on ROA, but managerial ownership and institutional ownership and the number of commissioners do not have a significant effect.